2008
DOI: 10.1042/bc20080020
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic signalling by the c‐Abl tyrosine kinase in normal and cancer cells

Abstract: c-Abl is a non-receptor tyrosine kinase which is localized both in the nucleus and cytoplasm, and is involved in the regulation of cell growth, survival and morphogenesis. Although c-Abl nuclear function has been extensively studied, recent data also indicate an important role in cytoplasmic signalling through mitogenic and adhesive receptors. Here, we review the mechanisms by which growth factors promote cytoplasmic c-Abl activation and signalling and its function in the induction of DNA synthesis, changes in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
134
1
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(143 citation statements)
references
References 107 publications
(206 reference statements)
3
134
1
5
Order By: Relevance
“…32 Furthermore, no amplifications of any of the other tyrosine kinases that were evaluated were observed. It is noteworthy that, in nonrhabdoid solid tumors, c-Abl is coexpressed commonly with tyrosine kinase receptors like PDGFR or epidermal growth factor receptor, 33 which does not appear to be the case in rhabdoid tumors. Nevertheless, the observed expression of c-Abl in rhabdoid tumors provides a rationale for novel treatment concepts, such as specific tyrosine kinase inhibitors like dasatinib and imatinib.…”
Section: Discussionmentioning
confidence: 98%
“…32 Furthermore, no amplifications of any of the other tyrosine kinases that were evaluated were observed. It is noteworthy that, in nonrhabdoid solid tumors, c-Abl is coexpressed commonly with tyrosine kinase receptors like PDGFR or epidermal growth factor receptor, 33 which does not appear to be the case in rhabdoid tumors. Nevertheless, the observed expression of c-Abl in rhabdoid tumors provides a rationale for novel treatment concepts, such as specific tyrosine kinase inhibitors like dasatinib and imatinib.…”
Section: Discussionmentioning
confidence: 98%
“…However, it is possible that the Hippo pathway prevents proliferation through other mechanisms as well. Although this study focused on the apoptotic role of c-Abl, c-Abl is also a pro-proliferative factor (reviewed in Sirvent et al 48 and Colicelli 49 ). Activation of c-Abl in the cytoplasm is involved in the response to growth factors [50][51][52] and F-actin assembly.…”
Section: Discussionmentioning
confidence: 99%
“…5 Our group and other groups have reported that c-Abl plays an important role in oxidative stress-induced neuronal death. [6][7][8] Recently, Ko et al 9 and Imam et al 10 have reported that c-Abl phosphorylated Parkin and inhibited its E3 ligase activity that led to the neurotoxic accumulation of Parkin's substrates.…”
mentioning
confidence: 82%